2023
DOI: 10.1039/d3ta05364d
|View full text |Cite
|
Sign up to set email alerts
|

Ostwald ripening mechanism-derived MnOOH induces lattice oxygen escape for efficient aqueous MnO2–Zn batteries

Junjie Zheng,
Chenchen Qin,
Chi Chen
et al.

Abstract: Aqueous rechargeable MnO2-Zn batteries have attracted much attention in recent years due to their high security, low cost and environmentally friendly. Nevertheless, the practical application of MnO2 cathode materials is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
(92 reference statements)
0
2
0
Order By: Relevance
“… 53 Recently, this technique has been widely reported for the preparation of porous TM-based electrodes, including Oswald ripening and sub-stabilized-directed secondary growth. 54 This approach, which does not require an external template, dramatically simplifies the synthesis strategy. Oswald ripening refers to the partial dissolution of less stable internal structures in a solvent and their redeposition on the crystal surface, resulting in the formation of a variety of porous structures on the micrometre and nanometre scales.…”
Section: Synthetic Strategies and Conversion Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 Recently, this technique has been widely reported for the preparation of porous TM-based electrodes, including Oswald ripening and sub-stabilized-directed secondary growth. 54 This approach, which does not require an external template, dramatically simplifies the synthesis strategy. Oswald ripening refers to the partial dissolution of less stable internal structures in a solvent and their redeposition on the crystal surface, resulting in the formation of a variety of porous structures on the micrometre and nanometre scales.…”
Section: Synthetic Strategies and Conversion Mechanismsmentioning
confidence: 99%
“… 55 In the case of sub-stabilized-directed approved to secondary growth, it is the growth of crystals in the initially formed sub-stabilized state under thermodynamic conditions, which will further interact with the remaining reactants in the solvent, resulting in crystal growth. Zheng et al 54 prepared an MnOOH precursor through Ostwald ripening, and then induced the escape of lattice oxygen by heat treatment, ultimately resulting in the formation of oxygen-defect-rich β-MnO 2 nanorods. Meanwhile, DFT calculations showed that the oxygen defects can act as dopants, leading to better electrical conductivity in β-MnO 2 .…”
Section: Synthetic Strategies and Conversion Mechanismsmentioning
confidence: 99%